(untitled) (International Journal of Engineering and Computer Science, 2017)
All types of liquids require a media to store them, in a civilized area these storage media are termed as liquid storage tanks. This storage tanks are made up of different materials and shape. In majority circular liquid storage tanks are used for storing waters in industrial and residential area, in petroleum refiners required circular tanks for storing crude oil, petrol, and kerosene, etc. As these are also one of the important structures, design engineers need to study the behavior of these tank under various load condition, for better performance of tanks and to minimize the disasters, loss of life during earthquake and to make the tank work even after the disaster. An attempt is made to study the behavior of liquid storage tank under three different cases namely- static analysis, frequency / modal participation analysis, time history analysis and dynamic analysis. By determining the responses of the tank such as fluid pressure, hoop stress, principal stresses, tank displacement and natural frequency, mode shape and deformed shape due to dynamic fluid pressure and velocity.